EVENT ORGANIZER STRATEGY OFFSET PRINTING DYNAMICS AS AN ENTERTAINMENT SERVICE PROVIDER - Ahmad Affandi; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to find out how the event organizer strategy Dinamika Offset Printing as an entertainment medium. As a theoretical basis in analyzing the problems in this qualitative research, theories about strategy, marketing communications and event organizers are used. The data collection technique used in this study is descriptive analysis method, namely interviews and observations and has primary data, namely the leader of the LPM Dinamika UIN SU Company and secondary data, namely the accountability report of the company division. The results of the research show that the event organizer strategy carried out by Dinamika Offset Printing is to notify their services through the events they create as well as promotions through social media. Keywords: Strategy, Event Organizer, Marketing Communication